HYDRATION EFFECTS ON THERMOREGULATION MECHANISMS DURING JUDO TRAINING (Fiep Bulletin - online, 2015)
Introduction: Thermoregulation  has an important role in body homeostasis. Thermal stress can modify the level of activation of cognitive processes responsible for the motor perception and actions, leading to performance reduction. Moreover, dehydration can significantly increase  rectum temperature and cardiac heart rate, reducing sweat production, V02max. and the exercise performance, in comparison with conditions of normal hydration. As judo is a sport modality practiced at enclosed environment with heavy and thick clothes, the jodgui, the heat loss can be reduced, compromising the athlete performance, mainly on training programs.  Aims:  study the effects of  hydration in the thermoregulatory mechanisms during the training of judo athletes. Method: the sample consisted of 10 judo athletes with more than five years of practice (average age of 17 years and 18.46% of corporal fat). The athletes appeared for two training days consisted of a habitual  judo training, duration of 1 hour and 40 minutes, following four days of regular training and a 48 hours rest. Subjects were divided in two experimental balanced groups,  a) hydrated (HJ - the athlete ingested 200 ml of water every 15 minutes during the training) and b) not hydrated (NHJ - the athlete did not ingest water during the training). This study it was approved by the Committee of Ethics in Research of the UNIBH. During both training sections heart rate, tympanic temperature and sweating rate were accessed. The data were analyzed by pared Student "t" test (p
Keywords: Thermoregulation; hydration; Judo-Gui.